2015
DOI: 10.1039/c5ra13011e
|View full text |Cite
|
Sign up to set email alerts
|

Crucial factors in biosynthesis of fluorescent CdSe quantum dots in Saccharomyces cerevisiae

Abstract: Simple, controllable and repeatable procedures to biosynthesize CdSe in Saccharomyces cerevisiae are systematically demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…It is worth mentioning that, the reaction of P. vermicola BGRW culture with cadmium chloride (Tube 2) at ( Figure 13B) did not emit any fluorescence light under UV light which shows the quantum dots did not produce, unless the existence of cadmium and selenium ions together and the type of QDs were CdSe, not CdS. In addition, it is worth mentioning that the color of fluorescent lighting is different by various ratios, which showed that the concentration of materials effect on the size of the quantum as known, the fluorescent color differs depending on the QDs size similar to other results (Wu et al, 2015).…”
Section: The Effect Of Metal Ion Concentration On Cdse Qds Formationsupporting
confidence: 64%
See 3 more Smart Citations
“…It is worth mentioning that, the reaction of P. vermicola BGRW culture with cadmium chloride (Tube 2) at ( Figure 13B) did not emit any fluorescence light under UV light which shows the quantum dots did not produce, unless the existence of cadmium and selenium ions together and the type of QDs were CdSe, not CdS. In addition, it is worth mentioning that the color of fluorescent lighting is different by various ratios, which showed that the concentration of materials effect on the size of the quantum as known, the fluorescent color differs depending on the QDs size similar to other results (Wu et al, 2015).…”
Section: The Effect Of Metal Ion Concentration On Cdse Qds Formationsupporting
confidence: 64%
“…The flasks were incubated on a shaker at 110 rpm and 37°C for 24 h according to Suresh et al (2014) with slight modification. The synthesis of QDs was followed by visually observation of gradation color from red to orange-yellow formed in the culture, UV-Vis and fluorescence spectrums were also obtained as previously described (Wu et al, 2015).…”
Section: The Effect Of Seo2 and Cdcl2 Concentration On Cdse Qds Formamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to corroborating the findings of Cui et al regarding the use of yeast cells at their stationary phase of growth [ 65 ], Wu et al investigated the optimization of CdSe QD synthesis using live cells of S. cerevisiae by screening the impact of the time of addition, the amounts and incubation time of Na 2 SeO 3 and CdCl 2 with Na 2 SeO 3 [ 124 ]. In another study, Bao et al used the same species of yeast to carry out the fabrication of well-dispersed CdTe QDs of ~3.6 nm in diameter [ 8 ].…”
Section: In Vivo Biosynthesis Of Inorganic Nanomaterials Using Yeamentioning
confidence: 93%